2014
DOI: 10.1155/2014/649261
|View full text |Cite
|
Sign up to set email alerts
|

Dichotomous Effect of Caffeine, Curcumin, and Naringenin on Genomic DNA of Normal and Diabetic Subjects

Abstract: Nutraceutical compounds show antioxidant and prooxidant properties under stress conditions like cancer, diabetes, and other diseases. The objective of this study is to find the dichotomic behavior of caffeine, curcumin, and naringenin on DNA of diabetic and normal subjects in the presence and absence of copper, hydrogen peroxide, and complex of copper-hydrogen peroxide. Hydrogen peroxide releases hydroxyl free radicals (•OH) on oxidation of Cu (I) to Cu (II) through Fenton-type reaction to cause DNA damage. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Caffeine has been reported as a protective substance against cellular damage with beneficial antioxidant effects [810]. Intake of caffeine is associated with reduced levels of biomarkers of oxidative stress [1115].…”
Section: Introductionmentioning
confidence: 99%
“…Caffeine has been reported as a protective substance against cellular damage with beneficial antioxidant effects [810]. Intake of caffeine is associated with reduced levels of biomarkers of oxidative stress [1115].…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin positively regulates cytoprotective and antioxidant proteins. However, it can induce a prooxidant effect at high doses [7]. One of the primary defense mechanisms against cytotoxicity is the stimulation of factor 2 related to erythroid nuclear factor 2 (Nrf2) and the activation of the antioxidant response element (ARE).…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin can positively regulate cytoprotective and antioxidant proteins. However, it has been shown that it can produce a pro-oxidant effect in high doses [6]. One of the primary defense mechanisms against cytotoxicity is the stimulation of Nrf2 activity and the activation of the antioxidant response element (ARE) Nrf2 signaling pathway, regulating the expression of genes involved in eliminating ROS [7].…”
Section: Introductionmentioning
confidence: 99%